Influencer marketing: current trends and prospects - K. A. Arzhanova; G. V. Dovzhik; V. N. Dovzhik (Вестник университета)
The article examines the influencer-marketing impact in the digital environment as one of the most popular lines of digital communications. The problem is the difficulty in recruiting a relevant blogger for promotional purposes. Methodologically, the study based on two basic psychological concepts: cognitive and interactive. The authors have conducted a critical analysis of scholarly literature and secondary documents and have addressed the concepts of blogger referentiality, identity and consumer identity statuses. The authors proposes and empirically verifies the hypothesis that the decision to buy an advertised product and the identity status of the consumer are interrelated. The empirical study was conducted using the author’s methodological toolkit, including an online survey using the Schneider Personality Survey. Based on the results of the study, recommendations are given for marketers to select bloggers for the target group of 18–24 year olds with different identity statuses in order to build a positive product brand. Suggestions for bloggers to interact with consumer groups with specified identity statuses are provided. Forecasts are given on the development of the influencer-marketing market, the demand for the blogging profession, the effectiveness of including the blogger’s inclusion in the company communications as potential partners, and the relationship between consumer engagement levels and social network.